Gallstone Disease and Bacterial Metabolic Performance of Gut Microbiota in Middle-Aged and Older Patients - Georgescu D; Ionita I; Lascu A; Hut EF; Dragan S; Ancusa OE; Ionita M; Calamar-Popovici D; Georgescu LA; Lighezan DF (International Journal of General Medicine, 2022)
Doina Georgescu,1 Ioana Ionita,1 Ana Lascu,2 Emil-Florin Hut,3 Simona Dragan,4 Oana-Elena Ancusa,1 Mihai Ionita,1 Despina Calamar-Popovici,1 Liviu-Andrei Georgescu,5 Daniel-Florin Lighezan1 1Center of Advanced Researches in Cardiovascular Diseases and Hemostaseology/Department of Internal Medicine I, University of Medicine and Pharmacy “V Babes”, Timisoara, Romania; 2Department of Functional Sciences, University of Medicine and Pharmacy “V Babes”, Timisoara, Romania; 3Department IX of Surgery I/Compartment of Hepatic-Biliary-Pancreatic Surgery, University of Medicine and Pharmacy “V Babes”, Timisoara, Romania; 4Department of Cardiology, University of Medicine and Pharmacy “V Babes”, Timisoara, Romania; 5Clinic of Obstetrics and Gynecology, “Pius Brinzeu” Academic Emergency County Hospital, Timisoara, RomaniaCorrespondence: Ioana Ionita, Center of Advanced Researches in Cardiovascular Diseases and Hemostaseology/Department of Internal Medicine I, University of Medicine and Pharmacy “V Babes”, 5 Gh Dima, Timisoara, 300079, Romania, Tel +40 723 539 800, Fax +40 256 490 626, Email mdioanaionita@yahoo.com Ana Lascu, Department of Functional Sciences, University of Medicine and Pharmacy “V Babes”, 2 Eftimie Murgu Plaza, Timisoara, 300041, Romania, Tel +40 745 803 821, Fax +40 256 490 626, Email analascu@yahoo.comBackground: Gallstone disease (GSD) is more commonly presented in aged people.Purpose: The purpose of the study was to explore the insights of metabolic performance of bacterial species from gut microbiota as well as the clinical background in middle-aged and elderly patients with GSD.Patients and Methods: This is an observational study concerning 120 research participants. Of those, 90 patients with symptomatic GSD addressed for cholecystectomy, average age 59.83 ± 15.32 years: 45 with cholesterol rich gallstones (CGSs), 45 with pigment gallstones (PGSs) and 30 healthy controls joined this observational study. Clinical examination, lab work-ups, upper and lower digestive video-endoscopies, abdominal ultrasound/CT and gallbladder motility assessment by Dodd’s method were performed. Overall stool dysbiosis (DB) was assessed as 1 = minor, 2 = mild, 3 = severe, species being identified by matrix-assisted laser desorption ionization method. Stool samples from dysbiotic patients were analyzed by a next generation sequencing method with operational taxonomic unit identification.Results: Patients with GSD presented with a significant high range of overall gut DB (p < 0.0001) when compared with controls. Those with CGSs compared with those having PGSs displayed significant clinical differences related to elderly age, lifestyle and diet particularities, obesity, dyslipidemia, nonalcoholic fatty liver disease, hypertension, type 2 diabetes mellitus or impaired glucose tolerance, as well as motility disturbances of gallbladder with a decrease of the ejection fraction. Significant increase of overall DB range and alterations of several functional bacterial species with a decrease of butyrate, lactate, acetate/propionate and methane producers, mucin degrading bacteria, biodiversity index of microbiota, as well as an increase of lipopolysaccharide positive bacteria were significantly present in patients with CGSs.Conclusion: Middle-aged and elderly patients with GSD and a clinical background characterized by particular lifestyle, metabolic and gallbladder motility issues displayed significant modifications of biodiversity, overall gut DB and alterations of several functional bacterial species, with a decrease of their metabolic performance.Graphical Abstract: Keywords: biliary calculi, intestinal functional bacteria, dysbiosis